A meta-discursive analysis of online comments on the suggestion of cancelling National Matriculation English Test in China. Issue 3 (1st September 2020) - Yan, Xi
ABSTRACT: This study explores the ideologies of English in China through a meta-discursive analysis of online comments on Yang Li's suggestion that China's National Matriculation English Test should be cancelled. The analysis of netizens' comments shows that the ideologies of necessitation, externalization, and self-deprecation are in wide circulation in China. Although English is attached great importance in China, most of the Chinese people still view English as a language of the Other and themselves as illegitimate and incompetent users of English. It is hoped that this study can contribute to the current discussion on the status and functions of English in China by identifying the complexity of language ideologies surrounding English and shed new lights on English education in China.